Navigating Translation Rights: Expanding Access to Global Literature in Modern Education - Nodira Rustamova; Dilnoz Ruzieva; Umida Sharaxmetova; Leyla Burxanova; Umida Makhmudxodjayeva; Doniyorbek Imomniyozov; Azimjon Ibrokhimov (Qubahan Academic Journal)
This study aims to explore the complexities surrounding translation rights in educational contexts, with a focus on finding a balance between copyright protection and the need for greater access to foreign literature for educational purposes. Background. Translation rights present a significant challenge in educational settings, where access to foreign literature is essential for fostering cross-cultural learning and global understanding. However, restrictive copyright laws often limit the availability of translated works, creating barriers for educators and students alike. This issue is particularly relevant in an increasingly interconnected world, where access to diverse knowledge sources is critical to educational outcomes. Research Methods. A mixed-methods approach was employed, combining comparative legal analysis of international copyright laws, case studies of specific educational contexts, and surveys of educators to assess the impact of translation rights on their teaching and research. The study also examined potential solutions such as alternative licensing models and the use of technology-facilitated translations. Results. The findings reveal significant disparities in translation rights across different countries, with stringent copyright laws in some regions severely restricting educational access to translated works. Educators reported frequent challenges in obtaining necessary texts, often hindering their ability to provide a comprehensive global education. Conclusion. The study concludes that reforming translation rights is crucial to promoting global educational equity. It proposes a model that balances authors' rights with educational needs, emphasizing the role of alternative licensing frameworks and technology to facilitate broader access to translated literature. Addressing these issues is vital for fostering cross-cultural understanding and ensuring equitable educational opportunities.